Workplace training mediates safety culture towards patient safety - Lonatrista, Marcella Aprilia; Tj, Hery Winoto (Global Academy of Business Studies, 2025)
Purpose: This study aims to determine the effect of Safety Culture on Patient Safety, mediated by Work Training, among nurses in the Surgical Hospital CAP. The research focuses on how organizational safety values and continuous training contribute to reducing adverse events and improving healthcare service quality. Methodology: A quantitative approach was employed with a sample of 100 nurses selected through purposive sampling. Data were collected using structured questionnaires and analyzed through the Structural Equation Model (SEM) using Smart PLS to examine both direct and indirect effects among variables. Results: The results show that Safety Culture significantly affects Patient Safety (t = 2.657, p < 0.05), significantly influences Work Training (t = 14.962, p < 0.05), and Work Training significantly affects Patient Safety (t = 7.554, p < 0.05). Moreover, Work Training mediates the relationship between Safety Culture and Patient Safety (t = 6.775, p < 0.05). Conclusion: The findings confirm that Safety Culture directly and indirectly enhances Patient Safety through Work Training. A strong safety culture and ongoing professional development are essential for maintaining patient safety and comfort. Limitations: This study was limited to one hospital with a small sample, which may affect generalizability. Self-reported data may also introduce bias. Contribution: The research highlights the mediating role of Work Training between Safety Culture and Patient Safety, providing insights for hospital management to develop effective safety and training strategies.